Teknik Keamanan File Teks Menggunakan Kriptografi Dengan Algoritma One Time Pad Cipher - Fahlevi, Muhammad Reza; Dwiki Putri, Dini Ridha; Doni, Rahmad (STIKOM Tunas Bangsa Pematangsiantar, 2020)
Maintaining data that needs to be considered in system security is the authentication process. This process is carried out to ensure users who access data or information on the system are authorized users. There are several methods to authenticate, one of them using data encryption (cryptographic) techniques. Cryptography is applied to data or information by encoding or organizing the data needed only by those who have the key to which the data or information can be accessed. This research will implement the One Time Pad (OTP) algorithm to encode the data and information used. Data or information transferred in the application will form a ciphertext so that users will get a key to access the data or information. The making of this application is expected to guarantee the confidentiality and security of data properly, where the party that can access the original data or information is only the party that has the key.